PENGARUH PROFITABILITAS DAN KEPEMILIKAN KELUARGA TERHADAP PENGHINDARAN PAJAK (Study Kasus Perusahaan Non Keuangan Sektor Properti dan Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2019) - Maryam, Siti; Dewanti, Yopy Ratna (Jurnal Ilmiah Publika, 2022)
This research aims to analyze the effectivity and contribution of Local Taxes towards Local Own-Source Revenue in DKI Jakarta Province. The effectivity and contribution show the seriosness of regional government in exploring local own-source revenue for the development and working performance of the regional government. The research employs qualitative descriptive method as research methodology which show data without any manipulaton or changes. The source of data derived from Regional Revenue Agency of DKI Jakatya Province. The results reinforced that 2018 has higher effectivity level which are 103,23% and 2019 has lower effectivity level which at 90,485. On the other hand, 2019 has higher contribution level which are 88,23% and 2017 has lower contribution level which are 83,14%.